CENTRAL OBESITY AS A RISK FACTOR FOR TYPE 2 DIABETES MELLITUS. - Rambe, Ismatul Fauziah; Fellani, Brizelia Fellani; Octavia, Meta; Salsabila, Shafa (LPPMK STIKES Widyagama Husada, 2026)
Central Obesity, Characterized By The Accumulation Of Fat Around The Abdomen, Has Been Increasingly Recognized As A Significant Risk Factor For Type 2 Diabetes Mellitus (T2DM). This Systematic Review Aims To Evaluate Between Central Obesity And The Incidence Of T2DM. A Literature Search Was Conducted In July 2025 Using Databases Such As Pubmed, Google Scholar, And Ebsco. The Inclusion Criterias Are: Studies Published In The Last 10 Years, Available In Full Text, And Accessible For Free. Five Relevant Studies Were Reviewed And Synthesized. The Results Consistently Show That Indicators Of Central Obesity, Including Waist Circumference, Waist-To-Hip Ratio, Weight-Adjusted Waist Index (WWI), And Triglyceridemic Waist Phenotype, Are Strongly Associated With The Risk Of T2DM, Outperforming General Obesity Metrics Like BMI. The Visceral Fat Accumulation Plays A Critical Role In Insulin Resistance And Metabolic Dysfunction. These Results Draw Attention To The Value Of Central Obesity Measurements As Essential Components Of Early Detection And Prevention Strategies Aimed At Combating The Global Diabetes Burden.